AB0494 Early Clinical Experiences with Belimumab in Polish Patients with Systemic Lupus Erythematosus. (10th June 2014) - Majdan, M.; Kucharz, E.J.; Jeka, S.; Sierakowski, S.; Leszczyński, P.; Tł ustochowicz, W.; Olesińska, M.; Gł uszko, P.; Krężelok, M.; Suszek, D.; Kopeć-Mędrek, M.; Kolossa, K.; et al.
Abstract : Background: Belimumab is a monoclonal antibody, inhibitor of soluble B-cell activating factor, that is used in the adjuvant treatment of adult patients with active seropositive systemic lupus erythematosus (SLE) [1]. Belimumab was approved in Poland in 2011. Objectives: To analyze the influence of belimumab therapy on the severity of SLE (expressed as SLEDAI score) and glucocorticoid (GC) use in Polish patients qualified to Early Access Program (EAP). Methods: Recruitment to EAP was started in April 2012 in 8 Polish tertiary rheumatology centers. A total of 23 subjects were enrolled. The data of 22 patients (mean age 38.5±8.7 years, 18 women) with at least 3-month follow-up were analyzed. Median time elapsed between the diagnosis of SLE and the enrollment was 7 years (range: 1-39 years). Median SLEDAI score at baseline equaled 13.5 points (range: 6-32 points), and median baseline prednisone equivalent amounted to 11 mg (range: 5-35 mg). Results: Median SLEDAI score at 3 months (7 points, range: 3-14 points) was significantly lower than the respective baseline value (p<0.001). Moreover, a significant decrease in the median GC use was documented after 3 months of the treatment (down to 8 mg, range: 2-35 mg; p=0.033). The dose of GCs was reduced in 12/22 patients (median reduction: 33%, range: 17-67%). 13/22 patients continued therapy with belimumab for at least 12 months after the enrollment. Both median SLEDAI score (4 points, range: 0-13 points) and median GCs dose (7.5 mg, range: 0-40 mg) at 12 months were significantly lower than the respective baseline values (p=0.002 and p=0.033, respectively). The treatment was stopped in 4 cases due to remission (n=2) or other causes (surgery, pregnancy plans, n=2), or withdrawn due to its inefficacy (n=3), IgA deficit/leukopenia and infection (n=2). Conclusions: The obtained results point to the efficacy of belimumab in the management of SLE. Our findings are similar to those documented in the BLISS trial [2]. References: Ginzler EM, Wallace DJ, Merrill JT, et al. Disease control and safety of belimumab plus standard therapy over 7 years in patients with systemic lupus erythematosus. J Rheumatol. 2013 [Epub ahead of print]. van Vollenhoven RF, Petri MA, Cervera R, et al. Belimumab in the treatment of systemic lupus erythematosus: high disease activity predictors of response. Ann Rheum Dis. 2012 Aug;71(8):1343-9. Acknowledgements: GlaxoSmithKline provided support for data analysis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2880